Simultaneous electrochemical determination of hydroquinone, catechol and resorcinol at Nafion/multi-walled carbon nanotubes/carbon dots/multi-walled carbon nanotubes modified glassy carbon electrode - Wei, Chan; Huang, Qitong; Hu, Shirong; Zhang, Hanqiang; Zhang, Wuxiang; Wang, Zhaoming; Zhu, Menglin; Dai, Pingwang; Huang, Lizhang (Electrochimica acta, 2014)
[Display omitted] •We developed a Nafion/MWCNTs/CDs/MWCNTs electrode to detect HQ, CC and RS simultaneously.•The electrode was applied to detect HQ, CC and RS in the tap water, well water and river water.•The detection limit for HQ, CC and RS were 0.07μM, 0.06μM and 0.15μM (S/N=3). In this work, an excellent electrochemical sensor based on Nafion/multi-walled carbon nanotubes/carbon dots/multi-walled carbon nanotubes (Nafion/MWCNTs/CDs/MWCNTs) for simultaneous determination of hydroquinone (HQ), catechol (CC) and resorcinol (RS) in 0.1M phosphate buffer solutions (PBS, pH=7.0) was found. The functioned MWCNTs, which contained amido bond, were combined to CDs via the electrostatic interaction to build the Nafion/MWCNTs/CDs/MWCNTs modified electrode. As we know, MWCNTs have large specific surface area and CDs have electrical conductivity, which were benefited to build the composite modified electrode. The three dihydroxybenzene isomers could well separate from each other at the scan rate of 100mVs−1 with a potential difference of 119mV and 419mV for the oxidation peak potentials of HQ–CC and CC–RS, respectively. Differential pulse voltammetry (DPV) was used for the simultaneous determination of HQ, CC and RS in their ternary mixture. The peak current obtained was linearly dependent on the HQ, CC and RS concentrations in the range of 1.0 to 200.0μM, 4.0 to 200.0μM and 3.0 to 400.0μM and the detection limits for HQ, CC and RS were 0.07μM, 0.06μM and 0.15μM (S/N=3), respectively. The modified electrode was applied to detect the tap water, well water and river water and the recoveries of tap water, well water and river water samples were 100.3–109.8% for HQ, 96.0–105.8% for CC and 83.4–101.6% for RS, respectively.